The Comparative Study of Coping Styles and Hope among Narcotic Anonymous and Methadone Maintenance Treatment Members - Ali Beygi; Mohammad ali Mohammadyfar; Mohammad naghi Farahani; Shahram Mohammadkhani (Research on Addiction, 2012)
Introduction: Narcotic Anonymous (NA), and related 12-steps program have predominant influence on drug abuse treatment programs. The aim of this study was to compare coping styles and hope among Narcotic Anonymous and Methadone Maintenance Treatment members. Method: In this causal-comparative study, 100 male (50: NA, 50: MMT. Age: 20-40, minimal clean: 6 mounth), from Shahrood city completed coping styles scale, and hope scale. Findings: Results showed that Mean scores of Agency thinkig, Task-oriented copig style, and Avoidance-oriented coping style, in NA members was significantly high, from MMT members. Also, results of Discriminant Analisis showed that comparative differences between this samples were highlited in compound of variables. Conclusion: It seems that actively attendance in NA may enhances effective Coping style and hope.